"To condemn the Revolution is to condemn Christ": Radicalization, Moral Redemption, and the Sacrifice of Civil Society in Cuba, 1960. - Guerra, Lillian (Hispanic American Historical Review, 2009)
The article examines the discursive process of radicalization which occurred in the Cuban Revolution in 1960. It argues that events and conflicts in the realm of Catholic ideology and discourse helped catalyze support for policies of subversion and commitment in militant ways against larger trends to increase civil society. Ways of interpreting the radicalization and the decision of President Fidel Castro to "go Communist" are cited. It is concluded that the radicalization gained popular legitimacy and took root in the consciousness of citizens through leaders' engagement of this ream of symbols and belief.